Substance Abuse among Students Residing in University Dormitories - جلوب, منى جبار (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study aims to identify the impact of drug use in female students’ dormitories by analyzing the psychological and social factors involved. A descriptive analytical approach was used, based on a questionnaire distributed to a sample of female students residing in university dormitories. The results showed a clear negative impact on academic performance and social relationships, with various motivations for drug use, such as psychological pressure and environmental influences. The study recommends intensifying awareness programs and enhancing psychological and social support services in these environments.